Pengaruh Tunjangan Profesi dan Motivasi Kerja Terhadap Kinerja Guru - Dewi Kartini; Muhammad Kristiawan (Universitas Kristen Satya Wacana, 2019)
This study aims to determine whether there is the influence of professional allowance and work motivation on teacher performance. The population in this study were all high school teachers in the District of Muara Sugihan (55 teachers). The sampling technique used was proportionate stratified random sampling. The sample consisted of 2 groups: teachers who had received professional allowances and who had not received professional allowances. The sampling technique uses a sample size determination table developed by Isaac and Michael, for a population of 55 people with an error rate of 5%, a sample of 48 people. The results of data analysis show that (1) there is a significant effect between professional allowances on teacher performance by 25.3%; (2) there is a significant effect between work motivation on teacher performance variables with an influence of 47.0%; (3) there is a significant effect between the professional allowance and work motivation together on the teacher's performance of the Public High School in Muara Sugihan District at 57.0%.